Peritoneal metastases after laparoscopic ovarian cystectomy for ovarian teratoma with unexpected somatic-type malignancy - Chan Hon Chui; Lele Aung (Elsevier, 2021)
Laparoscopic ovarian cystectomy has been an accepted treatment for benign ovarian teratoma. We report a 10-year-old girl who developed peritoneal metastases after laparoscopic ovarian cystectomy for benign-looking ovarian teratoma that contained an unexpected somatic-type primitive neuroectodermal tumor. She underwent aggressive cytoreductive surgery, chemotherapy, autologous stem cell transplantation and radiotherapy, and achieved remission. We should consider avoiding the laparoscopic approach for ovarian cystectomy in children and adolescents with suspected ovarian teratoma.